Role of integrons, plasmids and SXT elements in multidrug resistance of Vibrio cholerae and Providencia vermicola obtained from a clinical isolate of diarrhea - Rajpara, Neha; Kutar, Braj M. R. N. S.; Sinha, Ritam; Nag, Dhrubajyoti; Koley, Hemanta; Ramamurthy, Thandavarayan; Bhardwaj, Ashima K. (Frontiers in Microbiology, 2015)
The isolates of Vibrio cholerae and Providencia vermicola obtained from a diarrhoeal patient were investigated for genetic elements governing their drug resistance phenotypes. Out of fourteen antibiotics tested, V. cholerae Vc IDH02365 isolate showed resistance to nine antibiotics, while P. vermicola Pv NBA2365 was found to be resistant to all the antibiotics except polymyxin B. Though SXT integrase was depicted in both the bacteria, class 1 integron was found to be associated only with Pv NBA2365. Integrons in Pv NBA2365 conferred resistance to β-lactams, aminoglycosides and trimethoprim. Pv NBA2365 carried two transformable plasmids imparting distinct antibiotic resistance traits to their Escherichia coli transformants. In rabbit ileal loop assays, Pv NBA2365 did not show any fluid accumulation in contrast with Vc IDH02365 that showed high fluid accumulation. To the best of our knowledge, this is the first report of a highly drug resistant P.vermicola and additionally co-existence of multidrug resistant V. cholerae and P. vermicola. Both the microbes appeared to possess a wide array of mobile genetic elements for a large spectrum of antimicrobial agents, some of which are being used in the treatment of acute diarrhoea.